ASSOCIATION BETWEEN FAMILY-CENTERED COUNSELING AND INTRAUTERINE DEVICE (IUD) UPTAKE: A CROSS-SECTIONAL STUDY IN GIRSANG SIPANGAN BOLON SUBDISTRICT, INDONESIA - Yeni Trisna Purba; Santi Widya Purba; Dini Pajriani Khairunnisa (International Archives of Medical Sciences and Public Health, 2026)
Intrauterine device (IUD) uptake remains suboptimal in Indonesian primary care, partly due to limited family involvement in contraceptive counseling. This study examined the association between family centered counseling and current IUD uptake among couples of reproductive age. A cross-sectional study was conducted at a Family Planning Counseling Center in North Sumatra, Indonesia. Thirty eligible couples, recruited by total sampling, were allocated into two naturally occurring groups (15 family-centered; 15 standard counseling). Associations were analyzed using Chi-square or Fisher’s exact tests; the primary outcome was expressed as an odds ratio (OR) with 95% CI, and Bonferroni correction was applied to secondary analyses. Current IUD use was reported by 86.7% (13/15) of the family-centered group versus 40.0% (6/15) of the standard group (OR = 9.75, 95% CI: 1.59–59.70, p= 0.023). Only family knowledge remained significant after correction (p = 0.001). Given the small, non-randomized sample, findings are exploratory and warrant larger prospective confirmation.